Migrations saisonnières et procédures d’identification dans l’Apennin septentrional à l’époque napoléonienne - Francesco Saggiorato (Association Paul Langevin, 2019)
This article analyses the phenomenon of seasonal migrations in the northern Apennines during the Napoleonic era. Through a multi-scale approach, attentive to the various issues of the migration experience, it examines cross-border mobility, and the conditions of seasonal migrants both during the preparation for their departure and while abroad. This article also considers the migratory phenomenon from the perspective of the relations between the State, its administrations and the mobile populations of the northern Apennines. Finally, it highlights the Napoleonic strategy for the control of seasonal migratory flows, which aimed at regulating the passage of migrants to the Maremma and, conversely, to the Kingdom of Italy, through various surveillance mechanisms.